The Role Of Social Media On Students’ English Vocabulary Achievement - Hanan, Ahmad; Yuliani, Neni; Suadiyatno, Taufik (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to explain the extent of the role of social media on students' English vocabulary mastery and also to describe the role of social media on students' vocabulary acquisition related to their respective use of social media. It uses the case study method. The data needed for this study were collected from student observations and questionnaires. Data were collected from direct observation and analyzed using descriptive qualitative methods to find out how to explain social media activity to students. By using this method, researchers can find out the average activeness of students on the most frequently used social media. This observation was also carried out to find out between social media activity and student vocabulary achievement. Meanwhile, the data collected from the questionnaire results were then analyzed using the descriptive data method and the classification method of social media activity from Nuraini (2011). This method was used to describe students based on their social media activity.Therefore, the results of this study indicate that there is student activity and vocabulary achievement so that social media plays an important role in achieving student vocabulary. However, some of the students have differences with different levels of social media activity. Most of the students with higher social media activity were able to achieve better vocabulary than those with lower social media activity, although there were some students with lower social media activity who could achieve better scores than those who were very active. . These conditions indicate that social media has a role in students' vocabulary mastery. As a researcher, I suggest that teachers and students try to use social media as a medium for language learning